2018
DOI: 10.1016/s2214-109x(18)30060-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence against children in South Africa: a nationally representative cross-sectional study of prevalence and correlates

Abstract: UBS Optimus Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
112
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 18 publications
14
112
4
3
Order By: Relevance
“…There were four studies in the USA [47][48][49][50], three in the UK [51][52][53], two in Hong Kong [54][55] two in Taiwan [56][57], and two in Germany [58,59]. There was one study in Denmark [60], the Netherlands [61], Switzerland [62], Japan [63], Suriname [64], Saudi Arabia [65], Israel [66], South Africa [67], and Hungary [68]. In the Balkans study [46], eight met eligibility criteria based on the number of types of maltreatment studied: Albania, Bosnia & Herzegovina, Bulgaria, Croatia, the Former Yugoslavian Republic of Macedonia, Greece, Romania, and Serbia; in general for our purposes, we treat these as one study.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There were four studies in the USA [47][48][49][50], three in the UK [51][52][53], two in Hong Kong [54][55] two in Taiwan [56][57], and two in Germany [58,59]. There was one study in Denmark [60], the Netherlands [61], Switzerland [62], Japan [63], Suriname [64], Saudi Arabia [65], Israel [66], South Africa [67], and Hungary [68]. In the Balkans study [46], eight met eligibility criteria based on the number of types of maltreatment studied: Albania, Bosnia & Herzegovina, Bulgaria, Croatia, the Former Yugoslavian Republic of Macedonia, Greece, Romania, and Serbia; in general for our purposes, we treat these as one study.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Fourteen studies measured all five maltreatment types [47][48][49][50][51]53,[56][57]61,[64][65][66][67][68]. Of nine studies measuring four maltreatment types, seven omitted EDV [46,52,[58][59][60][62][63], and two omitted sexual abuse [54][55].…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[72] The emergence of gender differences in internalising problems occurs during adolescence, with girls suffering more than boys. [6,73] Boys and girls may react differently to violence exposure, [37] and gender may moderate the pathways between violence exposure and mental health difficulties and the role of parents and peers as buffers. [74] We therefore hypothesised that boys would endorse more externalising than internalising problems and that girls would report more internalising than externalising symptoms, but we expected similar reports of exposure to violence for males and females.…”
Section: Researchmentioning
confidence: 99%
“…5 It was identified in a household survey carried out in South Africa with 5631 girls and boys, that of the 2,497 participating girls, 14.61% had suffered some form of sexual abuse before the age of 18, and 3.59% had suffered acts practiced by a man attached to them. 6 In another study, 8194 high school students in Quebec and Montreal found a higher percentage of girls sexually abused (15.2%) than boys (4.4%). 7 It is recorded that in Brazil, 28.4% of girls attending emergency and emergency services were victims of sexual abuse.…”
mentioning
confidence: 93%